23-11c/7

Simple and best practice solution for 23-11c/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23-11c/7 equation:


c in (-oo:+oo)

23-((11*c)/7) = 0

(-11/7)*c+23 = 0

23-11/7*c = 0 // - 23

-11/7*c = -23 // : -11/7

c = -23/(-11/7)

c = 161/11

c = 161/11

See similar equations:

| 30=(2x+3)+x | | 8=-7+5w | | N^2+-7N+18=0 | | 9-2x/7=7 | | N^2+-15N+56=0 | | 27=-4d-1 | | 4y=20x+4 | | -9+10s=3+6s | | 2x+4w=6wx | | 2(p+3)+p-6=3p | | X/6-3=-11 | | 3d+7=3(d-3) | | 8=-4/7n | | 7x-4=4y | | 3r(2r+1)=21 | | N^2+-18N+17=0 | | 3log(x-5)=log(35-x^3) | | 4z/3-=2z | | 3(4x-1)(4x+3)=49x | | Y(n)=4.5n-8 | | -6r+10=-10+4r | | 49=-7/9x | | 3ln(x-5)=ln(35-x^3) | | 4x+2+6x+8=30 | | 1/9/5.40 | | 42=-(x-4) | | -8-4n=-3n | | 30+4x+2+6x+8= | | 1.4y+2.2=0 | | 10=3u+1 | | -4(x-12)-2=6 | | 3y-2+2y+7-y= |

Equations solver categories